Bamboo Fences as a Nature-Based Measure for Coastal Wetland Protection in Vietnam - Mai Van, Cong; Ngo, Anh; Mai, Tri; Dao, H. T. (Frontiers in Marine Science, 2021)
Climate change has induced sea-level rise and high intensity of storms which create high nearshore waves. These caused severe mangrove degradation and eroded along the coastal wetland areas in the Mekong Delta in Vietnam. Mangroves in the coastal wetland foreshore can withstand only some certain design storm waves and be able to grow under several certain submerged conditions. Therefore, reducing waves and shallowing wetland elevation for recovering mangroves and protecting them in an early birth state is important. Bamboo or melaleuca fences have been used as a nature-based solution to reduce waves and currents approaching the shore for these above purposes along Vietnamese Mekong deltaic coasts. This paper investigates wave transmitting through the bamboo fence system and assesses its effectiveness in protecting the mangroves. Waves were simultaneously measured at two locations for comparison: in front of and behind the fences. The result shows that the wave reduction by the fences is considerable, and sedimentation occurs rapidly in the shelter areas behind the fences, which is highly favorable for mangroves recovering and growing. Next, the empirical formulae for the wave transmission coefficient (Kt) through the fence have been proposed a relationship between the dimensionless wave-structures parameters, such as the relative water depth, the wave steepness, and the fence freeboard. The findings create a basic technical reference for designing a natural friendly based solution by using bamboo and/or wooden fences in coastal protection generally and protecting mangroves specifically. The outcome of the research contributes to narrowing an existing gap in Vietnamese design guidelines for coastal wetland protection and also facilitates the use of locally available eco-friendly materials for coastal management along the Vietnamese Mekong delta coasts.